Managing quality in the service sector - Asher, Mike (Lima Kogan Page, 1996)
The evolution of quality management. Competing technologies for improvement. An integrated framework for improvement. Turning a mission into an agenda for action. Understanding business processes. Using statistics to monitor process performance. Introduction to control charts. The construction of X and R charts. The X moving range chart. Understanding process capability. Monitoring processes for error. Self- measurement. Why performance measurement fails. Opportunities for innovation. Case study: Trumplington Health Authority.
Keywords: ADMINISTRACION DE EMPRESAS; GESTION; SERVICIOS